Fermentation quality, nutritive value and in vitro ruminal digestion of Napier grass, sugarcane top and their mixed silages prepared using lactic acid bacteria and formic acid. (1st September 2022) - Xie, Huade; Xie, Fang; Guo, Yanxia; Liang, Xin; Peng, Lijuan; Li, Mengwei; Tang, Zhenhua; Peng, Kaiping; Yang, Chengjian
Abstract: This study aimed to determine the fermentation quality, nutritive value and in vitro ruminal digestion of silages produced with mixtures of Napier grass (NG) and sugarcane top (ST) in five different ratios of fresh matter: 100:0 (N100), 75:25 (N75), 50:50 (N50), 25:75 (N25) and 0:100 (N0) with or without lactic acid bacteria (LAB) and formic acid (FA). The NG contained a higher crude protein (CP) content and buffering capacity, but lower dry matter (DM), organic matter, neutral detergent fiber, acid detergent fiber and water‐soluble carbohydrates contents than ST. The N25 silage fermented well, with a significantly higher lactic acid (LA) content ( p  < .05) and lower pH and NH3 ‐N concentration than those of other mixed silages ( p  < .05). The FA addition resulted in the highest CP content and lowest pH, LA, acetic acid (AA) and NH3 ‐N contents, while LAB addition resulted in the highest LA content compared with other treatments. Although in vitro DM digestibility (IVDMD) did not significantly differ among the mixed silages ( p  > .05), mixing with ST and adding LAB or FA increased the IVDMD. Gas production (GP) and AA content of N25 silages were significantly higher than those of other silages ( p  < .05). The LAB‐ or FA‐treated silages had higher IVDMD, GP, total volatile fatty acid and AA contents ( p  < .05) but lower pH compared with the control silage ( p  < .05). These results demonstrated that NG utilization improved upon mixing with ST due to the enhanced fermentation during ensiling, and the optimum mixing ratio for NG and ST was 25:75 on FM basis. Using LAB and FA as additives during ensiling can improve silage fermentation quality and in vitro ruminal digestion.